B2B: a paradigm shift from economic exchange to behavioral theory: a quest for better explanations and predictions - LaPlaca, P.; Vinhas da Silva, R. (Psychology and Marketing, 2016)
The development of industrial marketing theory has been largely characterized by descriptive approaches in the scrutiny of B2B marketing phenomena. In its pursuit for scientific legitimacy and credibility to academics and practitioners alike, research into B2B relationships as a subject of scientific enquiry will need to seriously engage into what can be termed a true paradigm shift, one that advances discovery in this area from sheer descriptive analysis and reporting to the development of explanatory schemata and theoretical frameworks of a kind that allow for more accurate prediction of underlying B2B phenomena. In so doing, theoreticians and practitioners alike will be better equipped to understand both current and emerging issues at hand as well as their implications to organizations across any geography, cultural context or business situation. Should this be attained with some degree of success, it will mean a reduction in ambiguity accruing to the decision-making of individuals in organizations, and thus a significant contribution to the overriding objective of corporate strategic planning and correspondent resource allocation.